1980
DOI: 10.1126/science.208.4444.609
|View full text |Cite
|
Sign up to set email alerts
|

Gutless Bivalves

Abstract: A new benthic species of the protobranch bivalve genus Solemya, from the northeastern Pacific Ocean, lacks a gut. It has no internal digestive enzymatic apparatus; nor is there any provision for the secretion of enzymes into the mantle cavity for extraorganismic digestion. The most likely nutritional mechanism for such an animal is the active absorption of dissolved organic molecules from the environment by the large ctenidial lamellae. These are well provided with blood, cleansed of sediment by cilia, and hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…As far as is known, the digestive system in all solemyids is either greatly reduced (as in S. velum) or completely absent (as in S. reidi; Reid and Bernard 1980). Similarly, the labial palps, flattened structures that help sort food particles during deposit feeding and that are highly developed in non-symbiotic protobranchs, are reduced in Solemya species.…”
Section: Adaptations-host Anatomy and Bacterial Ultrastructurementioning
confidence: 97%
See 1 more Smart Citation
“…As far as is known, the digestive system in all solemyids is either greatly reduced (as in S. velum) or completely absent (as in S. reidi; Reid and Bernard 1980). Similarly, the labial palps, flattened structures that help sort food particles during deposit feeding and that are highly developed in non-symbiotic protobranchs, are reduced in Solemya species.…”
Section: Adaptations-host Anatomy and Bacterial Ultrastructurementioning
confidence: 97%
“…For decades, researchers were particularly captivated by the question of how these organisms, in which the digestive system is either severely reduced or absent entirely (Pelseneer 1891; Reid and Bernard 1980), met their nutritional needs. Following the discovery of chemosynthetic endosymbioses in hydrothermal vent organisms, such as the tubeworm Riftia pachyptila, it became apparent that Solemya sp.…”
Section: Introductionmentioning
confidence: 99%
“…The digestive tract is primitively present in Bivalvia but greatly reduced in complexity in species of Solemyidae (Reid 1980;Reid and Bernard 1980), some Nucinellidae (but see discussion in Oliver and Taylor 2012) and some cardiids. This character was also coded by Giribet and Wheeler (2002: char.…”
Section: Alimentary System Characters (Figs 16-18)mentioning
confidence: 99%
“…(3) An even more advanced evolutionary step towards life in anoxic depths is detoxification of H,S by oxidation, as demonstrated in some interstitial animals from sands rich in hydrogen sulphide (Powell et al, 1979(Powell et al, , 1980, and -beyond this stage -the utilization of chemical energy bound in H2S for trophic metabolism through incorporation of chemo-autotrophic bacteria producing Calvin-Benson-cycle enzymes. This mode of direct CO2-fixation has been documented recently for some pogonophorans (Felbeck, 1981;Felbeck et al, 1981;Southward et al, 1981) and suggested also for the gutless bivalve genus Solernya (Reid and Bernard, 1980). Underneath its cuticle P. leukoderrnatus always harbours numerous gram-negative bacteria (Giere, 1981) of similar size as in pogonophorans (Cavanaugh et al, 1981;Southward et al, 1981).…”
Section: Discussionmentioning
confidence: 93%